MANAJEMEN PEMBELAJARAN AKIDAH AKHLAK DALAM MENINGKATKAN KECAKAPAN HIDUP ( LIFE SKILLS) DI SEKOLAH DASAR NEGERI 02 GUNUNG KERAMAT - efo kasiah; Abdul Adib; Rina Setya Ningsih (UNISAN JURNAL, 2024)
slamic education is a conscious, planned effort in preparing students to know, understand, live up to the process of believing in Islamic teachings in their lives, or it can be said that it is an attempt to change individual behavior in their personal lives, social life and the surrounding natural life through educational process that is based on Islamic values ​​so that later students are able, able and skilled in carrying out life as an effort to maintain their survival and development. This study aims (1) to find out how the implementation of Aqidah Akhlak Learning Management in improving Life Skills education is applied to the Perintis Adiluhur Vocational High School. (2) To find out the inhibiting and supporting factors in improving life skills at Perintis Adiluhur Vocational School. The research design used is a qualitative descriptive research method, emphasizing the strength of direct field observations and then analyzing data from existing data sources. The results of this study indicate that Islamic Religious Education and Life Skills are components that cannot be separated, because both are a unified whole in relation to life. This research also shows that the concept of life skills can be used as a new direction in Islamic education, by integrating several aspects of life skills with Islamic education. From the results of this study it can be concluded that the application of life skills can provide abilities, abilities and skills to students both in the fields of information technology and religion. As a provision to live their lives, it is hoped that each student will have personal, rational, social, academic and vocational skills that are integrated in Islamic education